Xylem cavitation resistance can be estimated based on time‐dependent rate of acoustic emissions. Issue 2 (22nd May 2015) - Nolf, Markus; Beikircher, Barbara; Rosner, Sabine; Nolf, Anton; Mayr, Stefan
Summary: Acoustic emission (AE) analysis allows nondestructive monitoring of embolism formation in plant xylem, but signal interpretation and agreement of acoustically measured hydraulic vulnerability with reference hydraulic techniques remain under debate. We compared the hydraulic vulnerability of 16 species and three crop tree cultivars using hydraulic flow measurements and acoustic emission monitoring, proposing the use of time‐dependent AE rates as a novel parameter for AE analysis. There was a linear correlation between the water potential (Ψ) at 50% loss of hydraulic conductivity (P50 ) and the Ψ at maximum AE activity (Pmaxrate ), where species with lower P50 also had lower Pmaxrate ( P < 0.001, R 2 = 0.76). Using AE rates instead of cumulative counts for AE analysis allows more efficient estimation of P50, while excluding problematic AE at late stages of dehydration.